2015
DOI: 10.1038/srep12048
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Aromatic Residues and Helices of Papiliocin in its Antimicrobial and Anti-inflammatory Activities

Abstract: A cecropin-like peptide, papiliocin, isolated from the swallowtail butterfly Papilio xuthus, possesses high selectivity against gram-negative bacteria. Since Trp2 and Phe5 are highly conserved residues in cecropin-like peptides, we investigated the role of Trp2 and Phe5 in antibacterial activity. Substitution of Trp2 and Phe5 in papiliocin with Ala (papiliocin-2A and papiliocin-5A) revealed that Trp2 is a key residue in its antibacterial activities. In order to understand the structural requirements for papili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 52 publications
1
71
0
Order By: Relevance
“…We performed phase-sensitive 2D experiments, including total correlation spectroscopy (TOCSY) and nuclear Overhauser effect spectroscopy (NOESY) using time-proportional phase incrementation. 8,9 50 and 80 ms MLEV-17 spin-lock mixing pulses were used for TOCSY experiments and for NOESY experiments, mixing times of 150 ms and 250 ms were used. The 3 J HN coupling constants were measured from the DQF-COSY spectra.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We performed phase-sensitive 2D experiments, including total correlation spectroscopy (TOCSY) and nuclear Overhauser effect spectroscopy (NOESY) using time-proportional phase incrementation. 8,9 50 and 80 ms MLEV-17 spin-lock mixing pulses were used for TOCSY experiments and for NOESY experiments, mixing times of 150 ms and 250 ms were used. The 3 J HN coupling constants were measured from the DQF-COSY spectra.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Bactericidal kinetics of peptides against E.coli showed that papiliocin completely and rapidly killed E.coli in less than 10 minutes at 2 × MIC concentration, while PapN permeabilized bacterial membranes less effectively than papiliocin. 10 The results imply that the Trp 2 and Phe 5 in the amphipathic N-terminal helix are important in the rapid permeabilization of the gram-negative bacterial membrane. In this study, to gain further insight into the structure-activity relationships, we determined the 3D-structures of PapN in 300 mM DPC micelles and investigated the interactions between DPC micelles and PapN.…”
Section: Introductionmentioning
confidence: 95%
“…9 In order to understand the structural requirements for papiliocin function and to design shorter and potent peptide antibiotics, we designed papiliocin analog, PapN (residues Arg 1 -Ala 22 from the N-terminal amphipathic helix). 10 PapN exhibited significant broad-spectrum antibacterial activities without cytotoxicity. Bactericidal kinetics of peptides against E.coli showed that papiliocin completely and rapidly killed E.coli in less than 10 minutes at 2 × MIC concentration, while PapN permeabilized bacterial membranes less effectively than papiliocin.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that papiliocin containing an N‐terminal helix sequence exhibited high levels of antibacterial activity comparable to that of melittin . Additionally, the aromatic residues Trp2 and Phe5 located in the N‐terminal α‐helix are crucial for papiliocin antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the aromatic residues Trp2 and Phe5 located in the N‐terminal α‐helix are crucial for papiliocin antibacterial activity. The N‐terminal helix region alone harbors activity, while only C‐terminal region did not show antibacterial activity . Furthermore, the C‐terminal region of intact papiliocin is crucial for its high selectivity against Gram‐negative bacteria .…”
Section: Introductionmentioning
confidence: 99%